Improving Student’s Professional Communication Abilities – A Part of Career Success? - Tănaşcu, Constantin-Iulian; State, Cristina; Ghinea, Raluca-Elena; Costache, Robert-Andrei (European Journal of Sustainable Development, 2020)
Communication is the essence of interpersonal relations. The outcomes of all the activities we carry out depend on how we communicate, and in spite of the fact that it is essential that we prove our communication skills, we are poorer and poorer at doing so. Our study aims at revealing whether and to what extent young graduates of Romanian universities are aware of the importance of acquiring, practising and improving their communication skills, the more so that such abilities are decisive when it comes to achieving success in one’s career. Our study was conducted between 2-13 May, 2019 on the basis of an online questionnaire. The research methodology used in order to achieve the objectives formulated in the study consists in quantitative research, by means of a survey supported via an online questionnaire. The analysis of the data collected by means of the questionnaire was done using techniques such as: frequency of occurence of the answers to the questions addressed to the participants in the study, multiple response analysis and, where appropriate, in order to enhance the interpretation of the results, the calculation of the interquartiles applied to the questions quoted on a 10 point Likert-type scale. The 195 answers received were validated, analysed and processed econometrically using the SPSS for Windows and ANOVA applications. On the one hand, We have noticed that universities do not ensure minimum training to the future graduates with respect to the acquisition and development of communication and negotiation skills. For this matter we intend to extend the study in the near future, to see if this is the result of a lack of concern/interest on the part of the universities and/or on the part of future graduates. At the same time, we have found that the future university graduates are not stimulated to become aware of the importance of developing their communication and negotiation skills or to actively participate in various forms of scientific interaction such as national or international scientific sessions, round tables, meetings with outstanding representatives of the business environment, etc. Obviously, we are aware of the limitations of our study. Thus, we consider that its addressability was rather restricted. The group of respondents included very young graduates of economic higher education institutions. On the other hand, the respondents were not previously selected, so that there is the risk that the points of view expressed would be based not only on experience, but on intuition. Extending the respondent base (both in terms of age/expertise and field of activity) is also and important point for future action. Finally, we have formulated several proposals meant to contribute, in our opinion, to giving more importance to the training and development of business communication and negotiation abilities as a prerequisite of career success. Keywords: career success, graduates, communication abilities, interpersonal relations